2018
DOI: 10.2147/ijn.s183796
|View full text |Cite
|
Sign up to set email alerts
|

Apically targeted oral micelles exhibit highly efficient intestinal uptake and oral absorption

Abstract: IntroductionPolymeric micelles (PMs) hold promise for improving solubility and oral absorption of poorly soluble drugs. Unfortunately, the oral absorption of PMs is also limited by intestinal epithelium. To improve the oral delivery efficiency of micelles, transporter-mediated micelles could enhance the transport efficiency across the epithelial barrier, and they have attracted more attention.MethodsPeptide transporter 1 (PepT1)-mediated micelles (Val-PMs/Phe-PMs) were designed by grafting valine (or phenylala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The in vitro release study showed sustained release of CU from CHCU and CHCSCU formulations compared with the free CU suspension, as illustrated in Figure 7 . It revealed a burst release in the first 3 h, followed by a sustained release of CU over 24 h. In contrast, approximately 80% of the free CU was found in the release medium, indicating that CU displayed a rather fast release, that the dialysis bag had no detention on drug release after 24 h, and that the CHCU and CHCSCU nanoparticles released less than 20% of their CU content after 3 h and approximately 40% after 24 h. This is in line with previous studies showing that about 20–40% of CU contents were released from nanoparticles, while about 80% of CU contents were released from free CU in the medium studied within 24 h [ 67 , 89 , 90 ]. The results suggest that CU molecules were well-encapsulated within the nanoparticles, hence enhancing CU stability, and were released in a controlled manner, hence providing sustained delivery.…”
Section: Resultssupporting
confidence: 90%
“…The in vitro release study showed sustained release of CU from CHCU and CHCSCU formulations compared with the free CU suspension, as illustrated in Figure 7 . It revealed a burst release in the first 3 h, followed by a sustained release of CU over 24 h. In contrast, approximately 80% of the free CU was found in the release medium, indicating that CU displayed a rather fast release, that the dialysis bag had no detention on drug release after 24 h, and that the CHCU and CHCSCU nanoparticles released less than 20% of their CU content after 3 h and approximately 40% after 24 h. This is in line with previous studies showing that about 20–40% of CU contents were released from nanoparticles, while about 80% of CU contents were released from free CU in the medium studied within 24 h [ 67 , 89 , 90 ]. The results suggest that CU molecules were well-encapsulated within the nanoparticles, hence enhancing CU stability, and were released in a controlled manner, hence providing sustained delivery.…”
Section: Resultssupporting
confidence: 90%
“…However, despite the amount of research on polymeric micelles, data regarding the uptake mechanisms and intracellular trafficking of these micelles remains behind. Furthermore, most research that investigated the endocytic uptake of polymeric micelles only analyzed the uptake of the drug, hence, only providing indirect evidence for nanocarrier uptake [47,[93][94][95][96][97][98][99][100][101]. As will be discussed below, this assumption may not always be correct, as the carrier and the load can separate upon the uptake.…”
Section: Uptake Mechanisms Of Polymeric Micellesmentioning
confidence: 99%
“…Tu et al synthesized Val-α-tocopherol-PEG (TSPG) or Phe-TPGS by conjugating Val or Phe to TSPG, and made their 15 nmsized PMs (e.g., Val-PM or Phe-PM). 67 After Val-PM bound to PEPT1, the formed Val-PM-PEPT1 complexes were internalized into the cells via a combination of clathrin-mediated endocytosis, caveolae-mediated endocytosis, macropinocytosis, or clathrin-/caveolae-independent endocytosis in Caco-2 cells (Fig. 8A).…”
Section: Peptide/amino Acid-decorated Nddssmentioning
confidence: 99%
“…Nevertheless, various NDDSs have been investigated to target GI transporters/receptors for Fig. 8 Detailed mechanisms of the entry, intracellular trafficking, and exocytosis of (A) some AA (Phe or Val)-or (B) some zwitterion-decorated NDDSs (Phe-PM, Phe-conjugated PM; 67 Val-PM, Val-conjugated PM; 67 GS-PP-PM, Gly-Sar-conjugated PM; 68 PLGA@PPP4K, PLGA/CB-PPO-PCB NP 69 ). CV, caveolae-mediated endocytosis; LR, lipid-raft-mediated endocytosis; MP, macropinocytosis; CL, clathrin-mediated endocytosis; CCI, clathrin/caveolae-independent endocytosis; ER, endoplasmic reticulum; GA, Golgi apparatus; AAT, amino acid transporter; LAT2, L-type amino acid transporter 2.…”
Section: In Vivo Therapeutic Potential and Challenges Of Gi Transport...mentioning
confidence: 99%